2014
DOI: 10.1136/annrheumdis-2013-204835
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genes related to bone formation and resorption and the extent of radiographic change in ankylosing spondylitis

Abstract: Objective To identify genetic associations with severity of radiographic damage in ankylosing spondylitis (AS). Method We studied 1537 AS cases of European descent; all fulfilled the modified New York Criteria. Radiographic severity was assessed from digitised lateral radiographs of the cervical and lumbar spine using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). A two-phase genotyping design was used. In phase 1, 498 single nucleotide polymorphisms (SNPs) were genotyped in 688 cases; thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 33 publications
3
49
1
5
Order By: Relevance
“…Syndesmophyte formation is not consistently preceded by observed erosion, sclerosis or squaring, making their biological relevance unclear. A recent study found that use of the cmSASSS rather than mSASSS increased complete agreement of scores from 69.7% to 81.4% (116). This study also found that cmSASSS remained highly correlated with mSASSS (r 2 > 0.96).…”
Section: Radiographic and Clinical Datasupporting
confidence: 63%
See 2 more Smart Citations
“…Syndesmophyte formation is not consistently preceded by observed erosion, sclerosis or squaring, making their biological relevance unclear. A recent study found that use of the cmSASSS rather than mSASSS increased complete agreement of scores from 69.7% to 81.4% (116). This study also found that cmSASSS remained highly correlated with mSASSS (r 2 > 0.96).…”
Section: Radiographic and Clinical Datasupporting
confidence: 63%
“…Consistent with mSASSS validation studies, if less than four corners were lacking scores, they were given the mean score for that vertebral segment (cervical or lumbar) (51). A 'contracted mSASSS' (cmSASSS) was used, scoring 0 for normal vertebral corners, erosion, sclerosis or squaring, 1 for a definite syndesmophyte, and 2 for each corner with a total bony bridge (116). Scores for erosion, and squaring were removed as they reduce inter-rater reliability (55,56).…”
Section: Radiographic and Clinical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them are involved in the regulation of immune responses suggesting these single nucleotide polymorphisms (SNP) might augment the auto-immunity (Table 1-1). Genes associated with radiographic progression include several MHC molecules, such as HLA-DRB1, HLA-B and HLA-DQA1, as well as other genes mainly involved in bone anabolic and catabolic pathways (Table 1-2) [7][8][9].…”
Section: -21 Genetic Factorsmentioning
confidence: 99%
“…[7][8][9] ... 8 arthritis, enteropathy-related spondylitis and arthritis, and undifferentiated SpA [2].…”
mentioning
confidence: 99%